Efektivitas Penggunaan Aplikasi SINOPEN dalam Mengurus Perizinan dan Non- Perizinan pada DPMPTSP Kota Padang - Zumardi, Sarah; Busman, Vanessya Putri; Wulandari, Wulandari; Feronika, Dini; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Implementation of E-Government has become one of the priorities in bureaucratic reform and improving the quality of public services. This is in line with Presidential Instruction no. 3 of 2003 concerning National Policy and Strategy for E-Government Development, which encourages government agencies to utilize advances in information technology in government processes. In this research, the method used is a descriptive qualitative method. This means that the data collected is not in the form of numbers, but rather the data comes from interview scripts, field notes, personal documents, memos and other official documents. The SINOPEN application (Non-OSS Licensing and Licensing Information System) was launched by the Padang City Investment and One-Stop Integrated Services Service (DPMPTSP) in March 2022 with the aim of making it easier for the public to process permits and non-permits online. Based on research results, currently the SINOPEN application limits the use of one account to only one use, which makes it difficult for users who frequently access the application during the licensing or non-licensing application process.